Persuasi, Perilaku Merokok, dan Preferensi Anak Muda terhadap Pesan Kampanye Berhenti Merokok - Rifka Sibarani; Yudi Perbawaningsih (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2018)
This research attempts to revisit the research on the youth preferences on several quit-smoking Public Service Advertisements (PSA). These preferences are including several factors, such as different form, structure, and content of persuasive messages. The objective of this research is to test the possibility of the linkage between the smoking behaviors and smokers’ preferences on various quit-smoking advertisements, with 104 university students who labeled themselves as smokers took part in the survey. The results show that respondents are mostly heavy smokers and they tend to have both the negative and positive attitudes towards smoking. On the other hand, all respondents have seen at least one quit-smoking PSA. This shows that quit-smoking PSAs are solely not adequately effective to change smoking behaviors. The respondents tend to favor the PSAs with less fear-appeal, more rational messages with statistics, and in the form of audio-visual.